The Use of Instagram Social Media as an Interaction Media in Shaping Adolescent Lifestyles - Lidya Cici Rahmayanti; Lutfi Zulfikar Fauzi (Journal Basic Science and Technology, 2021)
This study aims to determine the impact of the use of Instagram social media in shaping the lifestyle of teenagers in Kutamandiri Village. The method used is descriptive research that uses a qualitative approach. Based on the research results, Instagram is the dominant social media used by teenagers. Instagram has a very interesting feature so that teenagers often interact on Instagram. The results of this study are Instagram can shape the lifestyle of teenagers, because Instagram provides access for teenagers to express themselves freely in public. Teenagers' lifestyles change and they are formed from their interests and interests with lifestyles that become a place to exist for others.